1997
DOI: 10.1103/physreve.56.923
|View full text |Cite
|
Sign up to set email alerts
|

Noise-mediated enhancements and decrements in human tactile sensation

Abstract: Recently, it has been shown that noise can enhance the detection and transmission of weak signals in certain nonlinear systems. Here we demonstrate noise-mediated improvements in human sensory perception. We show that the ability of an individual to detect a subthreshold tactile stimulus can be significantly enhanced by introducing a particular level of noise. We demonstrate that this effect is robust over time. We also show that the ability of an individual to detect a suprathreshold tactile stimulus can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
133
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 31 publications
8
133
1
Order By: Relevance
“…Some studies have also reported that SR improves visual [9], aural [10] and haptic [11] ability. The SR effect in tactile sensitivity has also been confirmed in feet [12], [13], hands and fingers [14], [15], and improved tactile sensitivity is known to influence the sensorimotor functions of humans [7], [8]. It has further been reported that SR improves balance control in humans [16], [17].…”
Section: Introductionmentioning
confidence: 75%
“…Some studies have also reported that SR improves visual [9], aural [10] and haptic [11] ability. The SR effect in tactile sensitivity has also been confirmed in feet [12], [13], hands and fingers [14], [15], and improved tactile sensitivity is known to influence the sensorimotor functions of humans [7], [8]. It has further been reported that SR improves balance control in humans [16], [17].…”
Section: Introductionmentioning
confidence: 75%
“…This phenomenon has been demonstrated in the CNS (Gluckman et al 1996;Manjarrez et al 2002b;Durand 2000, 2001). In sensory systems, several SR type effects have been demonstrated in terms of the response amplitude or the signal-to-noise ratio of the output (Ando 2006;Bahar and Moss 2004;Collins et al 1996Collins et al , 1997Dhruv et al 2002;Hanggi 2002;Ivey et al 1998;Liu et al 2002;Manjarrez et al 2002aManjarrez et al , 2003Manjarrez et al , 2007Mori and Kai 2002;Moss et al 2004;Richardson et al 1998;Russell et al 1999;Ward et al 2002;Winterer et al 1999); however, there is no direct evidence about the existence of this phenomenon in the motor system.…”
Section: Introductionmentioning
confidence: 96%
“…It is found that the time delay τ 1 in the deterministic force can enhance tumor cell number, while the time delay In recent years, time-delayed stochastic processes have been the subject of increased interest in various fields. It was recently found that noise and delay can actually be an integral part of biological information processing [1,2]. Mainly, bistable systems with simultaneous noise and time delay have been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently found that noise and delay can actually be an integral part of biological information processing [1,2]. Mainly, bistable systems with simultaneous noise and time delay have been investigated in detail.…”
mentioning
confidence: 99%